(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study delivers a full insight into the current state of research on social responsibility and sustainability in developing countries. It aims to point out the relevance of social responsibility and sustainability issues, the need for their enhancement as the top priority for business entities. Furthermore, it also highlights ways to enhance sustainability and social responsibility in real estate industry of developing countries. The growth of real estate industry brings risks of unsustainability to developing countries. Thus, it is a must for real estate businesses to enhance a sustainable model of development through promoting sustainable leadership and integrating corporate culture. As such, the study is the first toemphasise the role of sustainable leadership in promoting sustainable model of development in the real estate industry of developing countries